2016
DOI: 10.1007/s00125-016-4004-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diet-induced lipodystrophic C57BL/6J mice with long-acting PASylated leptin normalises insulin sensitivity and hepatic steatosis by promoting lipid utilisation

Abstract: Aims/hypothesis Recombinant leptin offers a viable treatment for lipodystrophy (LD) syndromes. However, due to its short plasma half-life, leptin replacement therapy requires at least daily subcutaneous (s.c.) injections. Here, we optimised this treatment strategy in LD mice by using a novel leptin version with extended plasma half-life using PASylation technology. Methods A long-acting leptin version was prepared by genetic fusion with a 600 residue polypeptide made of Pro, Ala and Ser (PASylation), which enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Previous studies in LD mice showed no effects of leptin treatment on energy expenditure [ 20 , 21 ], body temperature [ 25 ], or on BAT mUcp1 mRNA expression [ 18 ]. The difference with the present study could be due to a number of methodological factors such as LD mouse model (AGPAT −/− mice in [ 20 ], conjugated linoleic acid-treated mice in [ 21 ], and Tg (A-ZIP/F-1) mice in [ 25 ]), the duration of leptin treatment (3-week infusion in [ 20 ], single injection in [ 21 ], and 1-week infusion in [ 25 ]), and/or the method to determine thermogenesis (48 to 80 h energy expenditure measurements in [ 21 , 25 ] and core body temperature measurements by telemetry following torpor induced by an overnight fast in [ 25 ]). The study of Shimomura et al [ 18 ] is the most similar to the present study since the authors also used Tg (aP2-nSREBP1c) mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in LD mice showed no effects of leptin treatment on energy expenditure [ 20 , 21 ], body temperature [ 25 ], or on BAT mUcp1 mRNA expression [ 18 ]. The difference with the present study could be due to a number of methodological factors such as LD mouse model (AGPAT −/− mice in [ 20 ], conjugated linoleic acid-treated mice in [ 21 ], and Tg (A-ZIP/F-1) mice in [ 25 ]), the duration of leptin treatment (3-week infusion in [ 20 ], single injection in [ 21 ], and 1-week infusion in [ 25 ]), and/or the method to determine thermogenesis (48 to 80 h energy expenditure measurements in [ 21 , 25 ] and core body temperature measurements by telemetry following torpor induced by an overnight fast in [ 25 ]). The study of Shimomura et al [ 18 ] is the most similar to the present study since the authors also used Tg (aP2-nSREBP1c) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin treatment to Tg (aP2-nSREBP1c) mice for 12 days was found to reduce food intake, body weight, plasma insulin, and glucose levels as well as liver fat, but had no effect on BAT mUcp1 mRNA expression as determined by Northern blot analysis [ 18 ]. Similarly, while numerous studies have consistently shown that leptin treatment markedly improves glucose homeostasis and fatty liver in various mouse models of LD [ 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], the effects on energy expenditure have been less positive. Specifically, leptin treatment did not affect energy expenditure in mice with LD from conjugated linoleic acid treatment [ 21 ] or deficiency in 1-acylglycerol-3-phosphate O-acyltransferase 2 (AGPAT2) [ 20 ] as well as body temperature in mice with LD due to overexpression of the transcriptional repressor A-ZIP/F-1 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this formulation was stable when stored for 22 months at −20°C, indicating how PASylation can contribute to the maintenance of biological stability [ 430 ]. Similarly, PASylation has contributed to the improved half-life and efficacy of numerous proteins including leptin [ 431 , 432 ], erythropoietin [ 433 ], Conversin [ 434 ] and clotting factor VIII [ 435 ].…”
Section: Applications In Drug Deliverymentioning
confidence: 99%
“…There are a number of mechanisms believed to contribute to the development of insulin-resistance in obese patients. These include, but are not limited to, systemic chronic inflammation and ectopic lipid deposition [7,9,30,31]. Visceral adipose tissue is known to function as both a paracrine and endocrine organ through the secretion of adipokines [10].…”
Section: Intermittent Fasting Weight Loss and Appetite Controlmentioning
confidence: 99%